VENTURE CAPITAL FUNDS AS AN EFFECTIVE INSTRUMENT TO SUPPORT AND DEVELOP THE REAL SECTOR OF THE ECONOMY (THE EXAMPLE OF SIBERIAN FEDERAL DISTRICT) - V. A. Trifonov; M. N. Bubin (Вестник Кемеровского государственного университета, 2014)
The paper is devoted to the assessment of regional venture capital funds of Siberian Federal District and in Russia as a whole. Being major investors in innovative companies, they need to develop not only in the central part of Russia, but also in other regions. This paper provides an assessment of the regional venture capital funds, considers the problems of their development and suggests measures to resolve them.